Coastlines at Risk of Hypoxia From Natural Variability in the Northern Indian Ocean. Issue 6 (12th June 2022) - Pearson, Jenna; Resplandy, Laure; Poupon, Mathieu
Abstract: Coastal hypoxia—harmfully low levels of oxygen—is a mounting problem that jeopardizes coastal ecosystems and economies. The northern Indian Ocean is particularly susceptible due to human‐induced impacts, vast naturally occurring oxygen minimum zones, and strong variability associated with the seasonal monsoons and interannual Indian Ocean Dipole (IOD). We assess how natural factors influence the risk of coastal hypoxia by combining a large set of oxygen measurements with satellite observations to examine how the IOD amplifies or suppresses seasonal hypoxia tied to the Asian Monsoon. We show that on both seasonal and interannual timescales hypoxia is controlled by wind‐ and coastal Kelvin wave‐driven upwelling of oxygen‐poor waters onto the continental shelf and reinforcing biological feedbacks (increased subsurface oxygen demand). Seasonally, the risk of hypoxia is highest in the western Arabian Sea in summer/fall (71% probability of hypoxia). Major year‐to‐year impacts attributed to the IOD occur during positive phases along the eastern Bay of Bengal (EBoB), where the risk of coastal hypoxia increases from moderate to high in summer/fall (21%–46%) and winter/spring (31%–42%), and along the eastern Arabian Sea (i.e., India, Pakistan) where the risk drops from high to moderate in summer/fall (53%–34%). Strong effects are also seen in the EBoB during negative IOD phases, when the risk reduces from moderate to low year‐round (∼25% to ∼5%). This basin‐scale mapping of hypoxic risk is key to aid national and international efforts that monitor, forecast, and mitigate the impacts of hypoxia on coastal ecosystems and ecosystem services. Plain Language Summary: Coastal "dead zones, " with vanishingly low oxygen levels, stress marine organisms, compress their habitats, threaten the sustainability of fisheries, and can lead to mass mortality of marine life. The northern Indian Ocean is particularly vulnerable due to natural physical processes that bring oxygen‐poor water onto the continental shelf from vast offshore regions of low‐oxygen, and biological processes that can intensify coastal dead zones. Alongside these natural processes, coastal dead zones in the Indian Ocean are also influenced by human activity, such as fertilizer use and waste water management. In this study we use a large set of observations in the northern Indian Ocean to quantify how natural processes trigger coastal dead zones seasonally, and how they increase or decrease the risk of coastal dead zones from year‐to‐year. This information, on where and when coastal dead zones are most likely to occur, is key to anticipate and mitigate impacts on ecosystems and economies. Key Points: Regions at higher risk of coastal hypoxia in the northern Indian Ocean are identified using coastal oxygen observations The Indian Ocean Dipole (IOD) can amplify or suppress the seasonal risk of hypoxia by modulating coastal upwelling/downwelling The risk is most amplified during positive IOD phases along the coast of the eastern Bay of Bengal